Serodiagnosis of visceral schistosomosis by using Schistosoma spindale whole worm antigen in bovines by enzyme linked immuno sorbent assay in Bengaluru, Karnataka - MURTHY, SREENIVASA; D’SOUZA, PLACID E; ISLOOR, K SHRIKRISHNA (The Indian Journal of Animal Sciences, 2014)
In the present study indirect ELISA was aimed to detect specific antibodies of Schistosoma spindale using whole worm antigen. Out of 250 serum samples screened in cattle, 46 were positive indicating 18.40% infection. Out of 250 serum samples screened in buffaloes, 40 were positive with 16.0% rate of infection. The overall sensitivity of this test was 77.27% and specificity 75%. Out of 12 serum samples collected from animals positive for fasciolosis, amphistomosis and hydatidosis to check for specificity in ELISA, 8 serum samples showed cross reaction with Fasciola and Amphistome infection.